Improvement of Catfish (Claris sp.) Production on Limited Land in Bukit Dempo Village, Belinyu - Sapto Andriyono; Patmawati Patmawati; Ahmad Fahrul Syarif; Mu’alimah Hudatwi; Muhamad Amin (Department of Aquaculture, 2022)
The potential of freshwater fisheries in Bangka Regency, Bangka Belitung Province, is sufficient to support fisheries activities in this area. An activity that is quite prominent is catfish farming using swamps and tarpaulin ponds on limited land. In this study, the analysis of cultivation activities was carried out on the Bukit Dempo community group who became partners in the national community service activities, in cooperation with Universitas Airlangga and Bangka Belitung University. Characteristics of the pond using a combination of fixed nets with a net diameter of 0.5 cm. In the pond also found water plants in the form of water hyacinth which is expected to be able to make a symbiotic use of the organic material that has been left behind from feed and catfish waste. The cultivation system is classified as semi-intensive with a combination of commercial feed with high protein (31-33%). The main problem in this cultivation system is low productivity and the lack of technology applied in an effort to increase production efficiency Furthermore, high production yields are marketed to Pangkal Pinang City and also to local areas around the Belinyu sub-district. Technical constraints include Motile Aeromonas Septicemia (MAS) due to the bacterium Aeromonas hydrophylla, which causes about 10% of mortality in commodities before harvest. There has been no treatment action in overcoming the disease, so it is necessary to be careful in avoiding death due to disease by observing catfish at the change of seasons.